2018
DOI: 10.3390/pharmacy6030073
|View full text |Cite
|
Sign up to set email alerts
|

Young Muslim Women Living with Asthma in Denmark: A Link between Religion and Self-Efficacy

Abstract: Asthma is a chronic respiratory disease that can be controlled with appropriate medicinal treatment. Adherence to pharmacological treatment is therefore critical. Self-efficacy plays a key role in adherence to medicine in chronic diseases, including asthma. Additionally, ethnic minorities have poor adherence to medicines. However, the impact of religion on self-efficacy and adherence is understudied. Therefore, the aim of this study was to explore the role of self-efficacy in adherence to asthma medicine treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 47 publications
(83 reference statements)
0
11
0
Order By: Relevance
“…The relationship between religion and asthma is uncertain. Rather it has been used to explain self-management behaviours, medication adherence and has been perceived as a coping strategy in asthma where studies have demonstrated either a potentially positive influence [ 46 , 47 ] or a negative effect [ 48 ]. The positive influence of religion on individual health appears to be mediated through provision of social ties and support, access to the social capital of religious groups, enhancing health promoting behaviours and positive emotions [ 49 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between religion and asthma is uncertain. Rather it has been used to explain self-management behaviours, medication adherence and has been perceived as a coping strategy in asthma where studies have demonstrated either a potentially positive influence [ 46 , 47 ] or a negative effect [ 48 ]. The positive influence of religion on individual health appears to be mediated through provision of social ties and support, access to the social capital of religious groups, enhancing health promoting behaviours and positive emotions [ 49 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…It gives people inner strength and provides spiritual guidance when facing stressful situations and uncertainties of life (de Guzman et al 2015). Spirituality also plays an important role as a coping strategy, reduces stress, and gives comfort (Druedahl et al 2018;Frouzandeh et al 2015). Furthermore, spirituality is positively related to perceived social support (Hill and Pargament 2003), which is one of the sources of self-efficacy beliefs (Adler-Constantinescu et al 2013).…”
Section: Spirituality and Self-efficacymentioning
confidence: 99%
“…Bandura (2003) states that the effect of spirituality on self-efficacy may depend on one's conception of divine agency. If the God-human relationship is viewed as a guiding, supportive partnership, in which a person looks toward the Supreme Being as a source of collaborative strength, it can foster a sense of personal self-efficacy (Bandura 2003;Druedahl et al 2018).…”
Section: Spirituality and Self-efficacymentioning
confidence: 99%
“…They used praying as an alternative to medicine for controlling their symptoms. 11 In China, ethnic minority patients with HF used less confrontation coping and more avoidance and acceptance resignation coping strategies. 12 A patient's attitudes and beliefs regarding health and disease are rooted in family and social values within an ethnocultural background.…”
Section: Introductionmentioning
confidence: 99%